2004
DOI: 10.1073/pnas.0405709101
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala stimulation modulates hippocampal synaptic plasticity

Abstract: Experience-dependent synaptic plasticity is a fundamental feature of neural networks involved in the encoding of information, and the capability of synapses to express plasticity is itself activitydependent. Here, we introduce a ''low-frequency burst stimulation'' protocol, which can readily induce both long-term potentiation (LTP) and long-term depression (LTD) at in vivo medial perforant path-dentate gyrus synapses. By varying stimulation parameters, we were able to build a stimulus-response map of synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…Under low or moderate stress conditions, both types of reinforcement of DG-LTP have been shown to depend on noradrenergic and cholinergic activation (Ikegaya et al, 1997;Jas et al, 2000;Frey et al, 2001;Straube et al, 2003) and can be modulated by the basolateral amygdala Izquierdo, 1994;Ikegaya et al, 1996Ikegaya et al, , 1997Almaguer-Melian et al, 2003, Nakao et al, 2004. After acute swim stress, we found that DG-LTP reinforcement was dependent on the activation of mineralocorticoid receptors (MRs) by binding of corticosterone .…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Under low or moderate stress conditions, both types of reinforcement of DG-LTP have been shown to depend on noradrenergic and cholinergic activation (Ikegaya et al, 1997;Jas et al, 2000;Frey et al, 2001;Straube et al, 2003) and can be modulated by the basolateral amygdala Izquierdo, 1994;Ikegaya et al, 1996Ikegaya et al, , 1997Almaguer-Melian et al, 2003, Nakao et al, 2004. After acute swim stress, we found that DG-LTP reinforcement was dependent on the activation of mineralocorticoid receptors (MRs) by binding of corticosterone .…”
Section: Introductionmentioning
confidence: 59%
“…Additional work is required to characterize specific properties of LTP modulation induced by different tetanization protocols. Nakao et al (2004) found that modulation of DG synaptic plasticity critically depends on the interplay of the stimulation strengths of the BLA and the perforant path. They propose a direct synaptic input from the BLA to the dentate gyrus via the lateral entorhinal cortex and lateral perforant path.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Therefore, as proposed by Benes,58 and based on the data reported in this study, one can hypothesize that the selective decrease in GABAergic inhibitory function observed in layer I of SZP PFC may be the consequence of a specific disorganization of the complex neuronal afferent network reaching GABAergic interneurons of layers I and II from the amygdala or other cortico-limbic regions. [58][59][60][61] In schizophrenia, the disorganization of the MD afferent network reaching the GABAergic interneurons of the deeper cortical layers may be less pronounced or localized to only a small subset of neurons such as the chandelier neurons, which have been shown to be dysfunctional in SZP. 23 Is DNMT1 overexpression in layer I cortical GABAergic neurons causally related to the decrease of GAD 67 and reelin?…”
Section: Dnmt1 Mrna Overexpression In Pfc Of Szp Is Restricted To a Smentioning
confidence: 99%
“…In contrast, the burst-spiking horizontal and bitufted cells of layers I and II receive on their dendrites both excitatory axon terminal projections from thalamus and cortico-cortical pyramidal neurons 53 and massive excitatory axon terminal projections from the basolateral nucleus of the amygdala. [58][59][60][61] It has been suggested that amygdalo-cortical or cortico-cortical excitatory inputs to layer I and II cortical GABAergic interneurons may help to suppress information arriving at distal pyramidal neuron dendrites and den-dritic spines directly from MD afferent synapses. 52,53 Therefore, as proposed by Benes,58 and based on the data reported in this study, one can hypothesize that the selective decrease in GABAergic inhibitory function observed in layer I of SZP PFC may be the consequence of a specific disorganization of the complex neuronal afferent network reaching GABAergic interneurons of layers I and II from the amygdala or other cortico-limbic regions.…”
Section: Dnmt1 Mrna Overexpression In Pfc Of Szp Is Restricted To a Smentioning
confidence: 99%
“…R. Soc. B 369: 20130148 the induction of such effects in both the hippocampus [43] and prefrontal cortex [44], albeit thus far only when the timing between amygdala stimulation and plasticity induction is short.…”
Section: Intercellular Pathwaysmentioning
confidence: 99%